The Assessment Report on the Concorde Jet Airliner - Chen, Fange (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This report presents a comprehensive analysis of the Concorde Jet airliner project, one of the most iconic and controversial international collaborations in the history of aviation. By applying frameworks such as PESTLE and stakeholder analysis, the study explores the technological breakthroughs, strategic motivations, and sociopolitical contexts surrounding the project. Although the Concorde represented a pinnacle of aeronautical innovation, it was plagued by significant challenges including high operational costs, environmental concerns, and limited market viability. Cultural and ethical issues—such as cross-national cooperation complexities, sonic boom disturbances, and fuel inefficiency—further compounded the project’s difficulties. Drawing lessons from Concorde’s eventual decline, the report offers strategic recommendations for future international project management, emphasizing the importance of stakeholder alignment, environmental sustainability, cultural coordination, and long-term planning in large-scale technological ventures.